Cross-sectional survey of changes in knowledge, attitudes and practice of mask use in Sydney and Melbourne during the 2020 COVID-19 pandemic - Abrar Ahmad Chughtai; C Raina MacIntyre; Holly Seale; Ashley Lindsay Quigley; Mallory Trent (BMJ Open)
Objectives Since mask uptake and the timing of mask use has the potential to influence the control of the COVID-19 pandemic, this study aimed to assess the changes in knowledge toward mask use in Sydney and Melbourne, Australia, during the 2020 COVID-19 pandemic.Design An observational study, using a cross-sectional survey, was distributed to adults in Sydney and Melbourne, Australia, during July–August 2020 (survey 1) and September 2020 (survey 2), during the COVID-19 pandemic in Australia.Setting and participants Participants aged 18 years or older and living in either Sydney or Melbourne.Primary and secondary outcome measures Demographics, risk measures, COVID-19 severity and perception, mask attitude and uptake were determined in this study.Results A total of 700 participants completed the survey. In both Sydney and Melbourne, a consistent decrease was reported in almost all risk-mitigation behaviours between March 2020 and July 2020 and again between March 2020 and September 2020. However, mask use and personal protective equipment use increased in both Sydney and Melbourne from March 2020 to September 2020. There was no significant difference in mask use during the pandemic between the two cities across both timepoints (1.24 (95% CI 0.99 to 1.22; p=0.072)). Perceived severity and perceived susceptibility of COVID-19 infection were significantly associated with mask uptake. Trust in information on COVID-19 from both national (1.77 (95% CI 1.29 to 2.44); p<0.000)) and state (1.62 (95% CI 1.19 to 2.22); p=0.003)) government was a predictor of mask use across both surveys.Conclusion Sydney and Melbourne both had high levels of reported mask wearing during July 2020 and September 2020, consistent with the second wave and mask mandates in Victoria, and cluster outbreaks in Sydney at the time. High rates of mask compliance may be explained by high trust levels in information from national and state government, mask mandates, risk perceptions, current outbreaks and the perceived level of risk of COVID-19 infection at the time.